Distribution and Characteristics of Rare Earth Elements in Uranium-Ore Deposits from Rirang Area, West Kalimantan Province, Indonesia - Adimedha, Tyto Baskara; Farenzo, Rayhan Aldizan; Sukadana, I Gde; Nugraheni, Rosmalia Dita; Pratiwi, Fadiah; Ciputra, Roni Cahya; Indrastomo, Frederikus Dian; Syaeful, Heri; Rachael, Yoshi (Badan Riset dan Inovasi Nasional, 2024)
Uranium and rare earth elements (REE) are essential elements for the development of green environmentally friendly, and sustainable energy. To meet the increasing demand for these raw materials, Indonesia has taken steps to explore and map potential deposits, including the Rirang Sector in Melawi Regency, West Kalimantan. However, the available information on the mineralization of these elements in the area is limited. Therefore, this study aimed to provide a detailed characterization on the petrology and geochemical characteristics of uranium ore and to synthesize the mineral genesis of uranium and REE-bearing ore in the Rirang Sector. The analytical methods used included petrography, micro-XRF, and geochemical analysis. The results showed that uranium mineralization was present in brannerites, uranophane, and swamboite associated with tourmaline and monazite ore. Similarly, REE concentrations were hosted by REE-bearing minerals, such as monazite, xenotime, and loparite. Geochemically, the uranium concentration in the monazite ore ranged from 1,110 – 28,440 ppm, while the total REE (TREE) concentration varied between 85,320 to 138,488 ppm. The formation of uranium and REE mineralization were due to the metasomatism process and its association with the Na-rich fluid of felsic intrusion. Notably, the weathering process did not enrich uranium and REE content in the soil but rather decreased it due to the leaching process and the absence of clay minerals capable of absorbing the REE cations on the surface of clay crystal structures.